2017
DOI: 10.1002/jcop.21894
|View full text |Cite
|
Sign up to set email alerts
|

Changing youth attitudes toward the police through community policing programming

Abstract: This article presents an evaluation of a community policing program designed to increase youths' positive attitudes toward the police. A total of 45 youth attended the program and were surveyed at 3 time points: before program commencement, after program completion, and after a 4-month follow-up time period. Four program outcomes were examined: global attitudes toward the police, perception of the police, distributive justice of the police, and perception of police discrimination. Overall, participation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Because attitudes are generally known to be a driver for behavior (Ajzen & Fishbein, 2005;Bohner & Dickel, 2011), the attitude toward citizen participation will most likely be related to actual participation in the police domain as well. Previous research, for example, showed a relationship between attitude toward police legitimacy and the willingness to participate among youths (Hinds, 2009), and a relation between the presence of community policing programs to increase positive contact between youth and the police and attitude (Leroux & McShane, 2017). Attitudes tend to be strong and resistant to change and bias because they are often based on values or are of personal relevance (Ajzen & Fishbein, 2005;Honkanen & Verplanken, 2004).…”
Section: Attitudementioning
confidence: 99%
“…Because attitudes are generally known to be a driver for behavior (Ajzen & Fishbein, 2005;Bohner & Dickel, 2011), the attitude toward citizen participation will most likely be related to actual participation in the police domain as well. Previous research, for example, showed a relationship between attitude toward police legitimacy and the willingness to participate among youths (Hinds, 2009), and a relation between the presence of community policing programs to increase positive contact between youth and the police and attitude (Leroux & McShane, 2017). Attitudes tend to be strong and resistant to change and bias because they are often based on values or are of personal relevance (Ajzen & Fishbein, 2005;Honkanen & Verplanken, 2004).…”
Section: Attitudementioning
confidence: 99%
“…While researchers have suggested that community policing and problem-oriented policing programs are likely to positively influence perceptions of police among youth (Anderson, Sabatelli & Trachtenberg, 2007;Friedman, Lurigio, Greenleaf, & Albertson, 2004;Leroux & McShane, 2017), this demographic is often overlooked in community policing practices (Forman, 2004). Yet, research suggests that since youth identities are in the process of development, encounters with the law can have a significant impact (Murphy, 2015).…”
Section: Young Individuals and The Policementioning
confidence: 99%
“…
A lack of provincial standardization for social media use by Ontario police officers has limited the progression and success of community policing among young populations. The abundant success of police-youth communications in-person is evident in studies from studies by Anderson et al (2007), Hinds (2007, and Leroux & McShane (2017); these results suggests that increased social media communications between youth and officers would prove beneficial.However, the barrier between the community policing principles outlined in Ontario's Mobilization and Engagement Model (MEM) and actual police practice echo structural issues that have plagued Ontario policing for decades. Recent literature from Hawkes (2016) and earlier literature from Leighton (1991) demonstrate the ongoing struggle to translate theory into practice.
…”
mentioning
confidence: 96%
“…A lack of provincial standardization for social media use by Ontario police officers has limited the progression and success of community policing among young populations. The abundant success of police-youth communications in-person is evident in studies from studies by Anderson et al (2007), Hinds (2007, and Leroux & McShane (2017); these results suggests that increased social media communications between youth and officers would prove beneficial.…”
mentioning
confidence: 96%